Domestication of Juaro in Floating Net Cages with Different Companior Fish - Arjuna A.P Situmeang; Usman M Tang2; Rusliadi Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted on August to October 2017 in Fish Seed Center Sei Tibun, Kampar. Thei aim of this research was to determine the exact of companior fish in accelarating of Pangasius polyuranodon in controlled enviroment as aquaculture. The size of Juaro was using 6-10 cm. The method was using the experimental method with five treatment and three replications, the treatment were P0 (Pangasius polyuranodon without companior fish), P1 (Pangasius polyuranodon with five Cyprinus carpio), P2 (Pangasius polyuranodonwith five Pangasius hypophtalmus), P3 (Pangasius polyuranodon with five Osteochilus hasselti), P4 (Pangasius polyuranodon with five Oreochormis niloticus). The data was analyzed by using ANOVA (P<0,05). The result showed that the best treatment was Pangasius polyuranodon with Pangasius hypophtalmus(P2) with Spesific growth rate 1,60%, Feed efficiency 14,33%, Survival rate 100% and most fast to response the feed. The water quality parameters consists of temperature was around 26,7-290C, dissolved oxygen (DO)4,0-59 ppm and pH 5,6-6,0. Keywords: Juaro (Pangasius polyuranodon), Domestication, Companior fish